The cognitive roots of multimodal symbolic forms with an analysis of multimodality in movies - Wildgen, Wolfgang (Frontiers in Communication, 2024)
Condillac's (1754) "Traité des sensations" is the philosophical background of modern discussions on the relationship between perception and multimodal communication. The differences between perception and communication and the transitions between them are discussed with a focus on odor and color. It becomes clear that even at this primary level, the complex interactions of different modalities are the precondition for effective and rich communication. The second part discusses Cassirer's "Philosophy of Symbolic Forms" as a relevant framework for multimodality studies. Basic aspects are first commented on with a focus on music and visual art. The interaction is even more complex and rich in the case of language; the difficulty of large symbolic forms is mainly due to semantic composition and only to a lesser degree to syntactic concatenation. The first must merge/blend different semantic spaces. It must allow for the plurality of levels of integration from the lexical level, the level of phrases and sentences, up to texts and discourse. The third part focuses on multimodality in film. It treats the representation of movement and action in (film) narratives, the visual perception and representation/communication of movement and action, and the integration of music, moving images, and language.